Apropriações de concepções de leitura do Pacto Nacional pela Alfabetização na Idade Certa (PNAIC) - Loose, Celina (2016)
This Master’s dissertation aimed at investigating the reading proposal of Pacto Nacional pela Alfabetização na Idade Certa – Pnaic (National Pact for Literacy at the Right Age, in Portuguese). The documental corpus of this study was based on the Pact books sent by Ministry of Education and on the plans that were developed by the teachers educators from Institution of University Education (IES, in Portuguese) of Federal University of Espírito Santo (Ufes, in Portuguese) and by the study supervisors under the responsibility of the Regional Superintendence of Education (SRE, in Portuguese) of Cariacica’s city for the implementation of the Continuing Education of the Pact, with an emphasis on the Portuguese language subject, in the year 2013. While studying the topic, the paper sought to understand the conceptions of reading legitimated by Pnaic and, subsequently, appropriations of these reading conceptions of the Pact for formator IES and how they were oriented to the reading work. In order to do so, this study also adopted Mikhail Bakhtin’s concept of dialogism as a theoretical assumption, which has the dialog and the meaning as main categories. In order to reach the aforementioned goals, this paper relies on a methodology that is characterized as a case study, carrying out a qualitative approach, and making use of the principles of the documental research. The analysis of Pacts’ notebooks demonstrated, mainly, out of the suggestions of activities, preferences for reading activities, such as: reading delight, information seek reading, reading as a form of text studying and reading as a pretext in order to enhance the discussions and the reflection on training of literacy teachers. The reading proposal of the Pact is based on a language conception that privileges reading practices which focus on the interaction between reader (subject) and the object (text). The plans used by IES//Ufes for training action revealed a reshaping of the theoretical referential, taking the teacher course member to participate in another theoretical basis, which caused the reflection on his conception of literacy and reading, understanding, so that reading, or the act of reading, entails discourse process for the production of senses. The senses are not in the text and not the author, but the reader, because it is he who determines the reading